2020
DOI: 10.1515/ract-2020-0078
|View full text |Cite
|
Sign up to set email alerts
|

Efficient removal of radiocobalt and manganese from their binary aqueous solutions by batch adsorption process using PAN/HDTMA/KCuHCF composite

Abstract: Simultaneous removal of radiocobalt and manganese by adsorption onto polyacrylonitrile/hexadecyltrimethylammonium bromide/potassium copper hexacyanoferrate (PAN/HDTMA/KCuHCF) composite was studied. The synthesized composite was characterized by Fourier-transformed infrared (FT-IR), thermogravimetric analysis (TGA) and X-ray diffraction (XRD). The influence of the solution pH was studied in the range 1.5–7.8 and the results showed the effectiveness of the synthesized composite for simultaneous adsorption of rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
(42 reference statements)
1
3
0
Order By: Relevance
“…The data obtained by the PHREEQC program (Fig. 7 B) revealed that Cs + and HCrO 4 − are the dominant species of Cs(I) and Cr(VI) at the optimum pH range, which agrees well with the data reported in the literature (Hamoud et al 2021;Nasanjargal et al 2021;Zhang et al 2021). Natural zeolites have been recognized as excellent adsorbents for cationic species such as Cs + (Belviso et al 2021;Eljamal et al 2019;Szala et al 2015).…”
Section: Proposed Adsorption Mechanismsupporting
confidence: 89%
See 3 more Smart Citations
“…The data obtained by the PHREEQC program (Fig. 7 B) revealed that Cs + and HCrO 4 − are the dominant species of Cs(I) and Cr(VI) at the optimum pH range, which agrees well with the data reported in the literature (Hamoud et al 2021;Nasanjargal et al 2021;Zhang et al 2021). Natural zeolites have been recognized as excellent adsorbents for cationic species such as Cs + (Belviso et al 2021;Eljamal et al 2019;Szala et al 2015).…”
Section: Proposed Adsorption Mechanismsupporting
confidence: 89%
“…By increasing the mass of CTABzeolite from 1 to 10 g/L, the adsorbed amount of Cs + is reduced from 0.18 to 0.02 mmol/g while that of HCrO 4 − is reduced from 0.36 to 0.04 mmol/g. This reduction in the adsorbed amounts is attributed to (i) the decrease of CTABzeolite surface area and the increase of the diffusion path length owing to particle aggregation (Hamoud et al 2021;Mahmoud et al 2019;Chen et al 2012), and (ii) the utilization of unsaturated adsorption sites, of the extra CTABzeolite particles, which is accounted during estimating the adsorbed amounts of the studied (radio)toxicants (Mahmoud et al 2019;Xing et al 2011). During the calculation of the adsorbed amounts of Cs + and HCrO 4 − ions using Eq.…”
Section: Effect Of Ctab-zeolite Massmentioning
confidence: 99%
See 2 more Smart Citations